Laboratory measurements of light scattering matrices for resuspended small loess dust particles at 532 nm wavelength. (May 2019) - Liu, Jia; Zhang, Yongming; Zhang, Qixing
Highlights: Scattering matrices for two loess samples collected from Chinese Loess Plateau (one of the Asian dust sources) were measured at 532 nm. Angular distributions of light scattering matrices for loess sampled from China and Hungary are similar and confined to limited domains. An average synthetic light scattering matrix which is targeted for loess dust was presented, from 441.6 nm to 632.8 nm wavelength. Abstract: The Chinese Loess Plateau (CLP) is one of the sources or a recharge station of Asian dust. In this study, scattering matrices for two loess samples collected from different regions of CLP were measured at a wavelength of 532 nm from 5° to 160° scattering angles. Other necessary characteristics were also analyzed, like particle size distribution, chemical composition, refractive index and micro morphology. Synthetic scattering matrices for different loess samples were defined over full angular range of scattering by combining Lorenz–Mie calculations as well as extrapolations or interpolations of measurement results. From the perspective of constructing an average scattering matrix suitable for loess, similarities and discrepancies between synthetic scattering matrices for loess samples collected from CLP and Hungary were analyzed. Although different light wavelengths were employed in experimental measurements of CLP samples and Hungary loess, matrix elements for these three samples show comparable angular distributions and are confined to relatively limited domains, respectively. Then, an average synthetic scattering matrix targeted for loess dust was proposed for spectral range from 441.6 to 632.8 nm, which is valuable for multispectral and multi-angle satellite remote sensing as well as radiative transfer calculations. When compared with average scattering matrix of different kinds of mineral dust proposed previously, it can be seen clearly that the domains covered by loess samples and various kinds of mineral dust are highly coincident, while the areas covered by loess samples are more narrow.